Usage of AI-Driven Utility Tools amongst Researchers of Andhra Pradesh Technical Institutes: A Survey - Bairagi, Mandira; Lihitkar, Shalini Ramdas (DESIDOC Journal of Library & Information Technology, 2025)
The growth of science and technology, particularly Artificial Intelligence (AI), is clearly having a big impact across numerous areas, with education and research being particularly prominent. By utilising these AI-assisted digital technologies, one can assist in achieving objectives more quickly and accurately than ever before. The study intends to better understand how researchers are utilising AI-driven technologies for scholarly communications, including their usability, effectiveness, awareness, and different adaptation challenges. An online survey was conducted among technical professionals in the Andhra Pradesh region to assess the use of AI-driven tools for their research communication in the era of digital transformation. A total of 350 questionnaires were distributed in 16 technical colleges via email and social media by using the random sampling method and out of these, 272 complete and 25 incomplete responses were received. The data shows that while human interaction is still crucial, artificial intelligence’s contribution to research articles is continuously rising. 40.44 % of the respondents regularly use AI-driven tools for their research, while 36.02 % of the respondents are highly familiar and 48.16 % are little familiar with them. AI tools are primarily employed for writing research articles and detecting plagiarism, showing slightly higher usage than others. The major obstacles to wider adoption are insufficient knowledge and confidence in AI technologies. Even though most respondents acknowledge the potential of AI-driven tools, there is still a lack of total faith in these technologies.